Mesenchymal stem cell exosomes therapy for the treatment of traumatic brain injury: mechanism, progress, challenges and prospects - Ming-wei Liu; Hua Li; Gui-fei Xiong; Bin-ran Zhang; Qiu-juan Zhang; Shu-ji Gao; Yan-lin Zhu; Lin-ming Zhang (Journal of Translational Medicine)
Abstract Traumatic brain injury (TBI) is a heterogeneous disease characterized by brain damage and functional impairment caused by external forces. Under the influence of multiple mechanisms, TBI can cause synaptic dysfunction, protein aggregation, mitochondrial dysfunction, oxidative stress, and neuroinflammatory cascade reactions, resulting in a high disability and mortality rate for patients and a heavy burden on families and society. Exosomes are cell-derived vesicles that encapsulate a variety of molecules, including proteins, lipids, mRNAs, and other small biomolecules. Among these, exosomes derived from mesenchymal stem cells (MSCs) have garnered significant attention owing to their therapeutic potential in the nervous system, offering broad clinical applicability. Recent studies have demonstrated that MSC-derived exosome injections in traumatic brain injury models effectively mitigate local inflammatory damage and promote nerve regeneration following injury. Owing to their small size, challenging replication, ease of preservation, and low immunogenicity, MSC exosomes are emerging as a promising therapeutic strategy for traumatic brain injury. This review explores the pathogenesis of traumatic brain injury, the underlying mechanisms of MSC exosome action, and the potential clinical applications of MSC exosomes in the treatment of traumatic brain injury. Graphical abstract